Etiopathology and Group Prevention of Cow Infertility in the Conditions of the Republic of Karakalpakstan - Eshburiev B. M; Rakhimov O. R (American Journal of Biology and Natural Sciences, 2025)
The article investigates the causes of infertility in cows kept in specialized livestock farms of the Republic of Karakalpakstan. The study revealed that during the dry period, cows often experience an unbalanced diet and a deficiency of vitamins and microelements; after calving, during the period of increased lactation, the cows’ need for nutrients, vitamins, and minerals is not met, which leads to the development of alimentary-climatic infertility.